Students’ Mathematical Communication Skills in Jigsaw with Neo Snake and Ladder Game Based on Self-Concept - Fadliansyah, Fauzi; Junaedi, Iwan; Sutarto, Joko (Universitas Negeri Semarang, 2020)
This study aims to determine the mathematical communication skills in terms of students' self-concept in the Jigsaw cooperative learning model assisted by neo snake and ladder game. The method used in this research is mixed method with concurrent embedded design. This research was conducted in class IV at SDN Sukaratu 4 and SDN Sukaratu 1 Pandeglang in the 2018-2019 school year. Data is collected by tests, questionnaires and interviews. The results showed that mathematics communication skills in terms of students' self concept varied. This is shown from 11 students with high self concept categories obtained mathematical communication skills results in the form of 7 high category students, 2 medium category students and 2 low category students, from 9 students with self concept category being obtained mathematical communication ability results in the form of 1 high category student , 7 students in the medium category and 1 student in the low category, then 5 students in the low self concept category obtained mathematical communication skills in the form of 4 students in the medium category and 1 student in the high category.